Analysis of Low Student Achievement in Fifth Grade of Elementary School - Dilvina, Siska; Witono, A. Hari; Safruddin, Safruddin (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
This study aimed to determine the internal and external factors that cause low learning achievement of fifth-grade students at SDN 1 Barejulat. Internal factors include intelligence, interests, talents, and motivation, while external factors include family, school, and community. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through interviews, observations, and documentation studies. Â Instrument using interview sheet. The data analysis technique used is data reduction, data presentation, conclusion, or verification. Test the validity of the data using extended observations, increasing persistence, source triangulation, technique triangulation, and time triangulation. The subjects of this study were fifth-grade students. The results of this study indicate that students who get low learning scores, are caused by the lack of intelligence, interests, talents, and motivations possessed by both of them. Besides that it is also influenced by the family environment, school environment, and environment. Low student motivation is due to studentsâ€™ high sense of laziness in doing assignments and the lack of motivation given by parents. The family environment is very closely related to learning achievement. This is related to the lack of attention and warmth in the students’ families themselves. Efforts made by teachers in improving the learning achievement of fifth-grade students at SDN 1 Barejulat are by creating a class atmosphere that is thick with the spirit to compete, and guiding students by holding additional lessons. In addition, the teacher also tries to communicate with the parents of these students so that they pay more attention to their children’s learning activities.